Implementation of One Door Integrated Service Policy in Bekasi Regency and Bekasi City of West Java Province - Budi Santosa; Muh Ilham; Sampara Lukman; Megandaru W. Kawuryan (Budapest International Research and Critics University, 2022)
The government has set a specific target regarding the improvement of the ease of doing business index. Facts on the ground show that the condition of licensing services is still faced with the performance of the apparatus, overlapping regulations, convoluted procedures, unclear completion times and high licensing costs, many requirements that must be met, unresponsive attitude of officers, inadequate facilities and services. Less supportive. Concretely, licensing issues that have given rise to legal problems Corruption faced by the Bekasi Regent is related to the Meikarta Mega Licensing project even though the service assessment status has reached Prima. The purpose of this study was to analyze the implementation of the one-stop integrated service policy and formulate a model for the implementation of the one-stop integrated service policy. This study uses the theory of policy implementation proposed by Grindle which consists of policy content and policy context. The research approach used in this research is a qualitative approach with a descriptive type of research. The data analysis technique used is data reduction and drawing conclusions. The results showed that the implementation of the One Stop Integrated Service Policy in Bekasi Regency and Bekasi City chose the same policy direction, namely the Public Service Mall as a brand of integrated service policy, but in reality even though it was centered on the Public Service Mall there were still many licenses that were not well communicated with the community so that there are still many process constraints, from the aspect of policy content there are also too many derivative technical policies that regulate, resulting in the ineffectiveness of the integrated service policy. The model generated from this research is a modification of the grindle policy model that can streamline policy implementation.